2021
DOI: 10.1186/s12967-021-03055-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tc17 cell levels and imbalance of naïve/effector immune response in Parkinson’s disease patients in a two-year follow-up: a case control study

Abstract: Background Neuroinflammation has been proved to play a role in dopaminergic neuronal death in Parkinson’s disease (PD). This link highlights the relevance of the immune response in the progression of the disease. However, little is known about the impact of peripheral immune response on the disease. This study is aimed to evaluate how immune cell populations change in untreated PD patients followed-up for 2 years. Methods Thirty-two patients with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
(70 reference statements)
1
9
0
Order By: Relevance
“…Compared to HC, PD patients showed a consistent decline of CD8 + Tn cells, which was also independent of the therapeutic agents. This result was in agreement with the latest studies performed in the United States and Mexico separately [ 38 , 39 ], suggesting the consistent changes of CD8 + Tn cells in PD among different races. As the proliferation of naïve T cells and their differentiation into memory T cells are related to cellular senescence [ 40 ], the decrease of CD8 + Tn cells may reflect abnormal aging in PD patients.…”
Section: Discussionsupporting
confidence: 93%
“…Compared to HC, PD patients showed a consistent decline of CD8 + Tn cells, which was also independent of the therapeutic agents. This result was in agreement with the latest studies performed in the United States and Mexico separately [ 38 , 39 ], suggesting the consistent changes of CD8 + Tn cells in PD among different races. As the proliferation of naïve T cells and their differentiation into memory T cells are related to cellular senescence [ 40 ], the decrease of CD8 + Tn cells may reflect abnormal aging in PD patients.…”
Section: Discussionsupporting
confidence: 93%
“…The NLR was calculated as absolute neutrophil count divided by absolute lymphocyte count. All patients were in the drug-naïve condition to exclude potential effects of anti-Parkinsonian treatment on the immunological profile [ 15 , 16 ]. At the time of enrollment, clinical examination was performed by neurologists with experience in movement disorders, and motor symptoms were assessed by using the Unified Parkinson’s Disease Rating Scale (UPDRS) part III and the Hoehn and Yahr (HY) scale [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Chen et al found a weak association between the percentage of CD4 + T cells and the levodopa equivalent daily dose [ 24 ]. In another study [ 45 ], the negative correlation between the levels of T cytotoxic cells 1 (CD8 + Tbet+IFN- γ +) and T cytotoxic cells 2 (CD8 + GATA3 + IL-13+) with the Hoehn and Yahr scale score was observed only in patients receiving treatment with levodopa, thus suggesting that levodopa could affect T cytotoxic cells. Furthermore, it should be noticed that human and murine lymphocytes express all the five subtypes of DR, and the DRD2 agonist sumanirole was able to inhibit the shift to the Th1 and Th17 phenotypes of CD4 + T cells obtained from MPTP-intoxicated mice [ 46 ].…”
Section: Changes Of Peripheral Cd4 + and Cd8 + T Cells In Pd Patientsmentioning
confidence: 99%